과산화수소 생산을 위한 광촉매 소재의 제작 - 문건희 (The Korean Ceramic Society, 2022)
Hydrogen peroxide (H2O2) has been widely utilized as an oxidant in diverse industries such as pulp and paper bleaching, chemical synthesis, wastewater treatment, fuel, etc., which has been supplied by anthraquinone process. However, this method needs explosive hydrogen and oxygen gases, high temperature/pressure, massive organic solvent, and noble metal catalysts. The photocatalytic production of H2O2 is cost-effective and environmentally-benign process since only oxygen, water, and light are required. In this review, titanium dioxide (TiO2) and graphitic carbon nitride (g-C3N4) as a representative UV- and visible-light-active photocatalyst, respectively, are discussed with overviewing various structure and surface modification techniques in order to improve the photocatalytic H2O2 production. Furthermore, recent studies based on the photoelectrochemical(PEC) H2O2 production are briefly mentioned to understand how the separation of redox-reaction is important to obtain a high apparent quantum yield. Finally, the review proposes the outlook and perspective on the photocatalytic H2O2 production to build-up decentralized wastewater treatment system.